Design study of natural fiber reinforced honeycomb panel for lightweight and portable shelter materials for typical Malaysian climate - Muhammad Zulkarnain; Tofrowaih, Khairul Amri; Ahmed, Yaseen Adnan (Polish Society of Composite Materials, 2022)
An evacuation shelter provides simple living facilities made of lightweight materials for repeated use and ensures that the shelters provide a safe and suitable long-term environment. Improving the shelter material in terms of thermal quality in the Malaysian climate is one requirement when evacuating victims to emergency shelters in open areas. The article aims to investigate the effect of using local natural fibers for composite honeycomb skin on the thermal and mechanical performance. The composite skin is a natural fiber processed in a concrete panel to make a honeycomb sandwich. This work introduces a model of natural fiber distribution embedded in a concrete panel, which is subjected to thermal analysis and three-point bending (TPB) to optimize the honeycomb structure. In order to understand the thermal interaction of the panel sheet for an insulating system, the model provides a six-level range of the number of fibers (100, 200, 300, 400, 500 and 600) to analyze the fiber network. The simulation demonstrated that improvement in the insulating panel of about 2.58% could be achieved by using the number of 600 coconut fibers, which is much lower compared to plain concrete. The morphology study successfully demonstrates the understanding of the fiber distribution and thermal absorption by the concrete. Moreover, the mechanical performance is also positively affected by using fiber in the panel, especially sugar cane, which achieved a 47% improvement. This successfully simulated model provides a promising solution to promote local products for shelter material applications.